Advanced Diffusion-Weighted Abdominal Imaging: Qualitative and Quantitative Comparison of High and Ultra-High b-Values for Lesion Detection and Image Quality. Issue 5 (May 2020) - Dreher, Constantin; Kuder, Tristan Anselm; König, Franziska; Paech, Daniel; Tavakoli, Andrej; Laun, Frederik Bernd; Flothow, Florian; Gnirs, Regula; Benkert, Thomas; Strecker, Ralph; Schlemmer, Heinz-Peter; Bickelhaupt, Sebastian
Abstract : Introduction: Magnetic resonance imaging (MRI) of the abdomen increasingly incorporates diffusion-weighted imaging (DWI) sequences. Whereas DWI can substantially aid in detecting and characterizing suspicious findings, it remains unclear to what extent the use of ultra-high b -value DWI might further be of aid for the radiologist especially when using DWI sequences with advanced processing. The target of this study was therefore to compare high and ultra-high b -value DWI in abdominal MRI examinations. Methods: This institutional review board–approved, prospective study included abdominal MRI examinations of 70 oncologic patients (mean age, 58 years; range, 21-90 years) examined with a clinical 1.5 T MRI scanner (MAGNETOM Aera, Siemens Healthcare, Erlangen, Germany) with an advanced echo planar DWI sequence ( b = 0, 50, 900, and 1500 s/mm 2 ) after ex vivo phantom and in vivo volunteer investigations. High b900 and ultra-high b1500 DWIs were compared by a qualitative reading for image quality and lesion conspicuity using a 5-point Likert scale with 2 radiologists as readers. The ratios of apparent signal intensities of suspicious lesions/normal tissue of the same organ (LNTRs) were calculated. Appropriate methods were used for statistical analysis, including Wilcoxon signed-rank test and κ statistic for interreader agreement analysis ( P < 0.05/0.0125/0.005 after Bonferroni correction). Results: Image quality was significantly increased with b900 as compared with b1500 DWI ( P < 0.001) despite using an advanced DWI sequence. A total of 153 suspicious lesions were analyzed. Overall reader confidence for characterization/detection of malignant lesions and, correspondingly, the LNTR (mean, 2.7 ± 1.8 vs 2.4 ± 1.6) were significantly higher with b900 than with b1500 DWI ( P < 0.001 and P < 0.001). The increased confidence of lesion recognition and LNTR in the b900 DWI remained significant qualitatively in lymphatic and hepatic lesions and quantitatively in lymphatic, pulmonal, and osseous lesions. Conclusions: Using high b -value DWI (900 s/mm 2 ) provided an improved image quality and also lesion conspicuity as compared with ultra-high b -value DWI (1500 s/mm 2 ) in oncologic abdominal examinations despite using advanced processing. Consequently, the value for additional ultra-high b -value DWI in oncologic examinations should be critically evaluated in future studies.